Edukasi Kesehatan Tanah pada Kelompok Tani melalui Pembuatan Plant Growth Promoting Rhizobacteria (PGPR) - Anjar Maharani; Ike Ratna Setyo Pratiwi; Muhammad Nasrulhaq; Sukma Agustin Dyan Tika (AKSILAR: Akselerasi Luaran Pengabdian Masyarakat, 2024)
Currently, inorganic fertilizers are still farmers' choice because they are considered more practical and quickly affect plant growth. However, using inorganic fertilizers in the long term will undoubtedly affect the health and quality of the soil. On the other hand, farmers are generally used to using inorganic inputs, causing dependence on chemical products, further increasing the decline in soil quality. A healthy level of soil quality needs to be maintained so that agricultural products can always be maintained and safe for human consumption. This community service activity aims to provide soil health education and farmers' knowledge of Plant Growth Promoting Rhizobacteria (PGPR) as a solution for maintaining soil quality and reducing the use of inorganic fertilizers. The activity results show that farmers are strongly motivated to maintain the quality and health of their soil. The PGPR product is still considered a new product that has never been implemented by the Mulyo farmer group in Gumukmas Village. Farmer group members have high enthusiasm for the PGPR products they make. The PGPR products made are expected to be able to increase production and reduce the effects of the use of inorganic fertilizers. Periodic assistance and application evaluation in the field needs to be carried out so that farmers understand the proper application technique.